Pengaruh Bermain Peran Mikro terhadap Kecerdasan Interpersonal - Rd. Ranie Damayanti; Myrnawaty Handini; Hapidin Hapidin (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
This study aimed at examining how much influence the role play activities on interpersonal intelligence in children group A at Kindergarten, Tangerang City. This research used the experimental method to know how far the influence of independent variable to bound variable. The dependent variable is the ability of interpersonal intelligence (Y) while the independent variable which is the variable of the micro role play (X) which consists of free micro role play (X1) and guided micro role play (X2). This study conducted in TK I Asy - Syukriyyah and TK I Jaya Winata on the second semester of academic year 2016/2017. The results showed that Fcount = 6.194 Ftable = 4.11 at significant level α = 0.05, thus H0 rejected and alternative hypothesis H1 accepted. It means that there are differences in interpersonal intelligence between groups of children who are given free micro role play with groups of children who are given guided micro role play are accepted. In conclusion, the interpersonal intelligence of a given child playing a free micro role is higher than that of a child who given a guided micro role play.